A hydroponic greenhouse fuzzy control system: design, development and optimization using the genetic algorithm - Hamid KHAFAJEH; Ahmad BANAKAR; Saeid MINAEI; Majid DELAVAR (Spanish Journal of Agricultural Research, 2023)
Aim of study: The design and development of a hydroponic greenhouse fuzzy control system.